An exercise in uncertainty : a memoir of illness and hope - Gluck, Jonathan (Harmony, 2025)
"At age thirty-eight, Jonathan Gluck, a new father with a promising journalism career, was shocked to learn he had multiple myeloma, a rare, incurable blood cancer. He was told he had eighteen months to live. That was more than twenty years ago. Gluck isn't just something of a medical miracle. He's also part of a growing population. Thanks to revolutionary medical advances, many cancers and other serious illnesses are no longer death sentences, but chronic diseases people can often live with for years. While doctors continue to look for "magic-bullet" cures, they can now extend patients' lives by slowing the progression of their diseases one treatment at a time. The result is a strange, new no-man's land between being sick and being well where Gluck and millions of others reside. In An Exercise in Uncertainty, Gluck maps this previously uncharted territory. Among the many vexing side effects of chronic illness he explores is uncertainty-never knowing from one day to the next how one's illness might change them physically, emotionally, spiritually. When you have an incurable disease, how do you cope with knowing that even when you're in remission, it will eventually return? How do you live with the anxiety, the fear, the near-constant awareness of your mortality? For Gluck, one surprising answer is fly fishing. If you're looking for peace in your own sea of uncertainty, it might be something else. As Gluck will be the first to say, cancer has absolutely nothing good to offer, but almost dying has taught him valuable lessons about how to live"-- Provided by publisher.